Psychosocial and diet-related lifestyle clusters in overweight and obesity. - Godoy-Izquierdo, Debora; Rodriguez-Tadeo, Alejandra; Lara, Raquel; Ogallar, Adelaida; Ramírez, Maria; Navarrón, Estefania; Arbinaga, Felix (2021)
This study explored intraindividual multidimensional profiles integrating psychosocial factors, namely, body image and satisfaction, weight-related self-stigma, positivity, and happiness, and behavioural-lifestyle factors, namely, adherence to a healthy diet, among Spanish adults with overweight or obesity. We further aimed to investigate the association of excess weight (i.e., measured body mass index, BMI) with the abovementioned multidimensional configurations. A convenience sample of 100 adult individuals (60% females) with excessive weight (69% overweight; 31% obesity) was recruited. They completed self-reports regarding the study variables, and their weight and height were measured. With a perspective centered on the individual, a cluster analysis was performed. Three distinct intraindividual psychosocial and diet-related profiles were identified: a group of healthy individuals with excess weight (46%); a group of individuals who were negatively affected by their excessive weight and showed the most distressed profile (18%); and a group of dysfunctional individuals who seemed to be excessively unrealistic and optimistic regarding their excessive weight and unhealthy lifestyles, but were troubled by their weight (36%). Furthermore, individuals in the affected cluster had higher obesity (mean BMI ± SD = 32.1 ± 3.7) than those in the clusters of healthy (28.0 ± 3.0) and dysfunctional individuals (28.1 ± 3.3) (p < 0.05). The results showed that there are specific psychosocial and lifestyle profiles in the adult population with excess weight and that there are relationships among psychological, behavioural, and body-composition factors. For clinical application purposes, it is important to account for the heterogeneity within individuals who are obese and to individualize the interventions, with a focus from weight change to the individual’s overall well-being